2009
DOI: 10.1186/1471-2199-10-1
|View full text |Cite
|
Sign up to set email alerts
|

Identification of suitable internal control genes for expression studies in Coffea arabica under different experimental conditions

Abstract: Background: Quantitative data from gene expression experiments are often normalized by transcription levels of reference or housekeeping genes. An inherent assumption for their use is that the expression of these genes is highly uniform in living organisms during various phases of development, in different cell types and under diverse environmental conditions. To date, the validation of reference genes in plants has received very little attention and suitable reference genes have not been defined for a great n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
181
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 250 publications
(197 citation statements)
references
References 66 publications
(58 reference statements)
11
181
2
Order By: Relevance
“…The coefficient of variation (CV) for the overall assay was 5.35% (total assay variability), which is within the range (from 3.4% to 11.6%) of values reported in previously for qPCR (Pfaffl et al, 2004). Overall, the X-fold variance values in this study are somewhat higher than the values that have been observed in other plant systems (e.g., Mukesh et al, 2006;Remans et al, 2008, Barsalobres-Cavallari et al, 2009. Besides laboratory working errors these higher values may indicate high levels of variability across peanut organs and tissues, and this variability may be partially explained by the fact that many housekeeping genes, like gapdh, are not only important for basal cell metabolism, but also participate in other cellular functions (Singh and Green, 1993;Ishitani et al, 1996).…”
Section: Descriptive Statistics Of the Reference Candidate Genescontrasting
confidence: 52%
See 2 more Smart Citations
“…The coefficient of variation (CV) for the overall assay was 5.35% (total assay variability), which is within the range (from 3.4% to 11.6%) of values reported in previously for qPCR (Pfaffl et al, 2004). Overall, the X-fold variance values in this study are somewhat higher than the values that have been observed in other plant systems (e.g., Mukesh et al, 2006;Remans et al, 2008, Barsalobres-Cavallari et al, 2009. Besides laboratory working errors these higher values may indicate high levels of variability across peanut organs and tissues, and this variability may be partially explained by the fact that many housekeeping genes, like gapdh, are not only important for basal cell metabolism, but also participate in other cellular functions (Singh and Green, 1993;Ishitani et al, 1996).…”
Section: Descriptive Statistics Of the Reference Candidate Genescontrasting
confidence: 52%
“…In Arachis, for example, the ubiquitin gene is sometimes used in qPCR studies as a stable housekeeping gene (e.g., Luo et al, 2005;Nobile et al, 2007). However, several reports have shown that the expression levels of these so-called housekeeping genes differ among different plant tissues and organs (Jain et al, 2006;Remans et al, 2008;Barsalobres-Cavallari et al, 2009). Furthermore, normalization to a single housekeeping gene can lead to invalid normalization, because many housekeeping genes, are not only important for basal cell metabolism, but also participate in other cellular functions that may vary under changing conditions (Singh and Green, 1993).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Various studies of different plant species have defined reference genes for different organs (Nicot et al, 2005;Jain et al, 2006;Gutierrez et al, 2008;Hu et al, 2009;Qi et al, 2010;Manoli et al, 2012) or different environmental conditions (Nicot et al, 2005;Reid et al, 2006;Barsalobres-Cavallari et al, 2009;Hu et al, 2009). However, few studies regarding the validation of reference genes in rice have been reported (Kim et al, 2003;Jain et al, 2006;Narsai et al, 2010;Wang et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Several reference genes, including those coding for biological products such as tubulins, actin, glyceraldehyde-3-phosphate dehydrogenase (GAPDH), phosphatases, albumin, cyclophilin, micro-globulin, ribosomal units (18S rRNA) or ubiquitin (UBQ) have been described in the literature (Foss et al, 2003;Rocha et al, 2013). The correct choice of reference genes is crucial to properly analyze the results of qPCR (Suzuki et al, 2000) and to measure and reduce the errors from variations among the samples (Barsalobres-Cavallari et al, 2009). …”
Section: Introductionmentioning
confidence: 99%